Muyocopronones A and B: azaphilones from the endophytic fungus Muyocopron laterale - Nakashima, Ken-ichi (Beilstein J Org Chem, 2020)
Two new azaphilones, namely muyocopronones A (1) and B (2), were isolated from the cultures of an endophytic fungus Muyocopron laterale ECN279. Their structures were elucidated by extensive spectroscopic analysis. Their absolute configurations were determined using the modified Mosher’s method and through comparisons of experimental and calculated electronic circular dichroism data. In addition, muyocopronone B (2) was found to exhibit a weak antibacterial activity against some Gram-positive bacteria.